Effect of adapting sustainable construction materials on houses in tropical climates: case study of S11 House, Selangor, Malaysia / Muhammad Zulhelmi Maimun, Farah Hanna Ahmad Fuad and Murni Zainal - Maimun, Muhammad Zulhelmi; Ahmad Fuad, Farah Hanna; Zainal, Murni (2023)
Practicing sustainability will not only enhance one’s quality of life, but also contribute in advancing social, economic, and environmental conditions. Tropical region is associated with year-round lengthy periods of sunshine, high temperatures, high relative humidity, and a lot of solar radiation (Karam M., 2014). These conditions have encouraged the construction industry to adapt sustainable building materials to face such extreme hot and rainy seasons throughout every year. Utilizing sustainable materials in building design will help in reducing a building's life cycle cost and worrying environmental impact (Sahlol, D. G, 2020). The main case study is to focus on the material used by S11 House, which has achieved the highest-level, Platinum rating, of Malaysia’s Green Building Index (GBI) award. This research identifies the underlying benefits of incorporating sustainable building materials, especially in tropical climate. The research was accomplished through the analysis of S11 House on related topics, included publications, websites, essays, theses, national and worldwide organisations on the topic, all of which supported the comprehension and articulation of ideas. In response, the study will give further understanding on the right materials to use that suits the weather and condition in tropical region.